2021
DOI: 10.1145/3449214
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Video Summarization

Abstract: While surgical videos are valuable support material for activities around surgery, their summarization demands great amounts of time from surgeons, resulting in the production of very few videos. We study the practices involving surgical video to motivate and inform the future design of tools for their summarization. Through interviews and observations in a feld study, we fnd that (1) video summaries provide an important support for surgery, being used for self-improvement, education, discussing cases, scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 64 publications
0
2
0
1
Order By: Relevance
“…Snyder et al [83] found in their survey that resident surgeons and medical students do not benefit from videos due to a lack of help in interpreting them. Esposito et al [17] and Avellino et al [5] reported that video-based coaching has a lot of potential in surgical education, but the time commitment is a significant barrier. Editing the videos to create effective learning materials can be time-consuming, and this can limit the use of video-based coaching in surgical education.…”
Section: Surgery Teaching and Learningmentioning
confidence: 99%
“…Snyder et al [83] found in their survey that resident surgeons and medical students do not benefit from videos due to a lack of help in interpreting them. Esposito et al [17] and Avellino et al [5] reported that video-based coaching has a lot of potential in surgical education, but the time commitment is a significant barrier. Editing the videos to create effective learning materials can be time-consuming, and this can limit the use of video-based coaching in surgical education.…”
Section: Surgery Teaching and Learningmentioning
confidence: 99%
“…The secondary task of giving input for controlling pointing or annotating, impose demands on an already cognitively taxed operator [3]. Surgery has been singled out as a domain that particularly struggles with this dual-task challenge [6,8], and in response, a diferent approach has been studied, of shifting the load of a more balanced communication to the remote trainer. Previous work by Semsar et al [39,40] has shown that training on the communication skills for appropriate use of telementoring tools could efectively convey remote instruction and mitigate the imbalance, although in a more recent study, the authors show that this has limitations as local trainees still show the need for virtual referencing, as well as ownership of the virtual annotations to manage them according to their needs as the task advances, and not when the trainer decided [41].…”
Section: Deictic Communication In Surgicalmentioning
confidence: 99%
“…Cependant, la création d'environnements virtuels avec des objets interactifs en 3D est coûteuse et peut ne pas toujours reproduire fidèlement les rapports anatomiques du corps humain. En comparaison, les vidéos sont plus faciles à produire, car les chirurgiens peuvent enregistrer des procédures réelles et les utiliser comme outils pédagogiques [3]. Des études ont montré que les vidéos permettent aux étudiants de visualiser des gestes techniques et les relations entre les structures, améliorant ainsi leur compréhension des procédures, ce qui a un impact significatif sur l'acquisition des compétences chirurgicales [1,2].…”
Section: Introduction Et Travaux Antérieursunclassified